A-Effects of Drugs on Spontaneous Contractions of Rabbit Jejunum - Iqbal, Sohail; Sultana, Ulfat; Sultana, Tajwar; Sultana, Tajwar; . , Sadeeqa; Irshad, Faiza; Sharwani, Farah Khan; Nishat, Mufassar (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To find out possible to determine effect of C. reflexa extract on spontaneous contractions of rabbit jejunum. Methods: Animal experimental in vitro study from 1st October 2017 to 30 September 2018 at Pharmacology experimental lab, Wah Medical College Wah Cantt. Study model was Isolated pieces of rabbit jejunum and ileum. Sampling Technique used was Simple Random. Tissue considered fit for experiment after initial equilibration and stabilization. Result: Three increasing concentrations (0.1mg/ml, 0.2mg/ml and 0.4mg/ml) of C. reflexa extract decreased the response to 3.83±0.40, 2.33±0.33 and 1.33± 0.21mm. Decrease in response was significant with p- value 0.04, 0.008 and 0.003 respectively. Conclusion: Freshly prepared aqueous solution of crude extract of C. reflexa decreases the amplitude of spontaneous contractions of isolated rabbit jejunum.